Synthesis, dielectric, magnetic, and photoluminescence properties of two new hybrid rare-earth double perovskites - Wang, Ze-Jie; Li, Long-He; Feng, Yan; Wang, Qin-Wen; Wu, Ling-Kun; Li, Jian-Rong; Ye, Heng-Yun (Frontiers in Chemistry, 2022)
Herein, two new organic-inorganic hybrid double perovskites (R3HQ)4CsSm(NO3)8 (1) (R3HQ = (R)-(-)-3-Quinuclidinol) and (R3HQ)4CsEu(NO3)8 (2) were synthesized and charactered. 1 and 2 exhibit obvious phase transitions at 379 K and 375 K, respectively, confirmed by differential scanning calorimetry (DSC) and variable temperature powder X-ray diffraction. The dielectric switching between high-dielectric and low-dielectric states make them have typical hybrid responsive dielectric material with thermally switchable dielectric constant. Furthermore, 1 and 2 showed attractive photoluminescence and paramagnetic behavior, and the fluorescence quantum yield of 2 reached 14.6%. These results show that compound 1 and 2 can be used as excellent candidates for multifunctional intelligent materials, which also provides a new way for development of multifunctional materials.